The associative property of addition is shown in equations where the order in which the evaluation is made does not change the result, providing the numbers remain in the same order. Option B demonstrates this.
Answer:
x = -6
Step-by-step explanation:
Solve for x:
-x/3 = 2
Multiply both sides of -x/3 = 2 by -3:
(-3 (-x))/3 = -3×2
-3×(-1)/3 = (-3 (-1))/3:
(-3 (-1))/3 x = -3×2
(-3)/3 = (3 (-1))/3 = -1:
--1 x = -3×2
(-1)^2 = 1:
x = -3×2
-3×2 = -6:
Answer: x = -6
Answer:
Below
Step-by-step explanation:
● -7x + 5y = 35
Add 7x to both sides
● -7x +7x + 5y = 35+7x
● 5y = 7x + 35
Divide both sides by 5
● 5y/5 = (7x+35)/5
● y = 1.4x + 7
The graph of the function:
Answer: X= 3
Step-by-step explanation:
x-4*x-2=0
+4. +4
—————-
x*x-2=4
+2. +2
——————
x*x=6
2x=6
/2. /2
—————-
x=3